A non-neurodegenerative REM parasomnia with immersive dreaming and dream-reality confusion: a case report - Biabani, Nazanin; Mulas, Martina; Mutti, Carlotta; Higgins, Sean; Ilic, Katarina; Benson, Joshua; Santic, Ana; Gnoni, Valentina; Drakatos, Panagis; Romigi, Andrea; Nesbitt, Alexander D.; Naismith, Sharon L.; et al. (Frontiers in Sleep, 2025)
BackgroundREM sleep behavior disorder (RBD) is characterized by loss of normal muscle atonia during REM sleep, often associated with dream enactment behaviors, and is typically a prodromal neurodegenerative condition in middle-aged and older adults. However, emerging case reports and case series suggest that not all RBD presentations follow this trajectory, particularly in younger individuals.Case presentationA case of 7-year history of vivid, immersive dreaming perceived as continuous with waking life, accompanied by persistent dream-reality confusion, is described. The patient frequently engaged in reality-testing behaviors and reported significant cognitive fatigue. Video-polysomnography confirmed REM sleep without atonia and a concordant dream re-enactment episode. Neuropsychiatric evaluation ruled out dissociative or psychotic disorders, and no evidence of neurodegenerative disease was observed.ConclusionThis presented case illustrates a potentially distinct, non-neurodegenerative REM parasomnia phenotype that underscores the need to expand current parasomnia classifications to better capture the diverse cognitive and metacognitive dimensions of REM sleep disorders. Moreover, potential mechanisms underlying the main features of this case, including immersive dreaming and persistent dream-reality confusion, are discussed in relation to hypothesized dysfunction in melanin-concentrating hormone (MCH) signaling.